2017
DOI: 10.4072/rbp.2017.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Ostrácodos de lagos someros de la región central de Argentina: implicaciones paleolimnológicas

Abstract: -OSTRACODS OF SHALLOW LAKES OF THE CENTRAL REGION OF ARGENTINA: PALEOLIMNOLOGICALIMPLICATIONS. Studies about ostracods in shallow lakes are very scarce in the Province of La Pampa, thus the objective of this work is to contribute to the knowledge of the species present in lentic environments, studying the distribution, abundance, and specific associations of ostracods. The samples come from four shallow lakes of the Pampean Region, Province of La Pampa, Argentina. Sampling was performed along transects perpend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Considering the clustering of taxa registered in this study, H. similis and H. incongruens, previously found in La Pampa (Kihn & Pall, 2013;Kihn et al, 2017), can tolerate a wide range of salinity and are widely distributed in South America (Ramírez, 1967;Martens & Behen, 1994;César et al, 2001;Laprida, 2006). Heterocypris incongruens, is a cosmopolitan species (Külköylüoğlu, 2013;Fernández et al, 2016) frequently found in Buenos Aires Province (Ramírez, 1967;Laprida, 2006) and Patagonia (Schwalb et al, 2002;Cusminsky et al, 2005;2011) that could be used as an indicator of water pollution (Van der Meeren et al, 2010).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Considering the clustering of taxa registered in this study, H. similis and H. incongruens, previously found in La Pampa (Kihn & Pall, 2013;Kihn et al, 2017), can tolerate a wide range of salinity and are widely distributed in South America (Ramírez, 1967;Martens & Behen, 1994;César et al, 2001;Laprida, 2006). Heterocypris incongruens, is a cosmopolitan species (Külköylüoğlu, 2013;Fernández et al, 2016) frequently found in Buenos Aires Province (Ramírez, 1967;Laprida, 2006) and Patagonia (Schwalb et al, 2002;Cusminsky et al, 2005;2011) that could be used as an indicator of water pollution (Van der Meeren et al, 2010).…”
Section: Discussionmentioning
confidence: 52%
“…Among the taxa found in the lowest-salinity lakes, C. incisa is widely distributed in subsaline, shallow, vegetated, and chlorinated sodium lakes of South America and Argentina (Ramírez, 1967;Martens & Behen, 1994;César et al, 2001;Laprida, 2006;Díaz & Lopretto, 2011;Kihn et al, 2017). These conditions were found in DMo, and LTE, which have coverage of Schoenoplectus californicus in the Pampean lakes bicarbonate predominates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostracods also showed the highest total values and a more continuous presence, supporting the idea of decreasing lake levels. In particular, L. cusminskyae dominated the assemblage, which, together with H. incrongruens, might also indicate oscillations in lake levels and subsequent conductivity variations (Kihn et al, 2017;Laprida and Valero-Garcés, 2009;Marquez et al, 2016). Lake level fluctuations with a progressive reduction of level from 1340 AD to 1900 AD are ascribed to drier conditions and frequent extreme events registered in the Pampean region during the LIA (Córdoba, 2012;Córdoba et al, 2014;Guerra et al, 2017;Piovano et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Se encontraron especímenes vivos en las lagunas bonaerenses de Chascomús, Salada Grande, Los Horcones, del Monte y en el Arroyo Grande (Laprida, 2006); en la laguna Asansa (Río Negro) (Coviaga, 2015) y en las lagunas Monte de Caldén, General Campos y Don Tomás (La Pampa) (Kihn et al, 2017b). La especie ha sido registrada en la provincia de Buenos Aires en sedimentos del Pleistoceno Tardío de la laguna Mar Chiquita (Ferrero, 2009) y de la cantera "Nicolás Vignogna III", en el partido de Marcos Paz (Iacona & Carignano, 2018) y en sedimentos holocenos de los ríos Napostá Grande (Bertels & Martínez, 1990Martínez, , 1997 y Quequén Grande (Ferrero, 1996;Zárate et al, 1998), las lagunas Hinojales (Prieto et al, 1998), La Brava (Plastani, 2016;, La Barrosa (Plastani, 2016;Plastani et al, 2019), Cabeza de Buey (Plastani, 2016) y Blanca Grande (López Blanco et al, 2021), los arroyos Chico (Plastani, 2016) y San Miguel (Ramos et al, 2019) y el Canal 15 (Laprida, 1998;Bertels-Psotka & Laprida, 1998).…”
Section: Distribución Geográfica Y Estratigráficaunclassified